Prevalence and antimicrobial resistance of Campylobacter species isolates in ducks and geese - Jamali, H.; Ghaderpour, A.; Radmehr, B.; Wei, K.S.C.; Chai, L.C.; Ismail, S. (Elsevier Sci. Ltd., 2015)
A total of 471 duck and goose intestinal content samples were collected from wet markets and were determined for the prevalence of Campylobacter spp. For the detected isolates, resistance to selected antimicrobial agents was identified. Campylobacter spp. was detected in 114/291 duck samples (39.2%) and 47/180 goose samples (26.1%). Among the 161 isolated Campylobacter spp., 85.7% and 14.3% were Campylobacter jejuni and Campylobacter coli, respectively. Resistance to ciprofloxacin (82.6%), tetracycline (77%) and nalidixic acid (75.2%) was particularly high in the tested Campylobacter isolates. However, all isolates were susceptible to gentamicin, neomycin, streptomycin, neomycin and ampicillin. The presence of Campylobacter spp., as well as the detection of multidrug-resistant isolates in this study, indicates that consuming of duck and goose meat might be a potential campylobacteriosis risk in this region. (C) 2014 Published by Elsevier Ltd.